2001
DOI: 10.1093/rheumatology/40.8.889
|View full text |Cite
|
Sign up to set email alerts
|

Limited endothelial E‐ and P‐selectin expression in MRL/lpr lupus‐prone mice

Abstract: The increase in E-selectin in the kidney may contribute to the development of glomerulonephritis. However, the lack of systemic E- and P-selectin expression may represent a protective mechanism which limits the interaction between leucocytes and the endothelium in the chronic inflammatory context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…However, the aforementioned molecular and cellular pathomechanisms of autoimmune lung injury differ, at least in part, from those of lupus nephritis because Icam-1 -deficiency as well as TNF-α antagonism protects MRL lpr mice from lung but not from kidney disease [39], [41]. Furthermore, P-selectin is only induced in lungs but not in kidneys upon immune stimulation with LPS [38] or, as we found here, in experimental SLE. The latter finding is of particular interest because PTX3 was recently identified as an endogenous P-selectin inhibitor that limits leukocyte recruitment to the lung [27].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, the aforementioned molecular and cellular pathomechanisms of autoimmune lung injury differ, at least in part, from those of lupus nephritis because Icam-1 -deficiency as well as TNF-α antagonism protects MRL lpr mice from lung but not from kidney disease [39], [41]. Furthermore, P-selectin is only induced in lungs but not in kidneys upon immune stimulation with LPS [38] or, as we found here, in experimental SLE. The latter finding is of particular interest because PTX3 was recently identified as an endogenous P-selectin inhibitor that limits leukocyte recruitment to the lung [27].…”
Section: Discussionmentioning
confidence: 53%
“…Kidney disease in autoimmune mice (and lupus patients) mainly develops from immune complex disease and depends on glomerular complement activation and macrophage recruitment [36]. By contrast, lung disease in MRL lpr mice involves the recruitment of CXCR3 positive T cells via local secretion of CXCL10 [37], and the endothelial expression of selectins [38] and intercellular adhesion molecule (ICAM)-1 [39]. In addition, TNF-α is a crucial mediator of lung injury in experimental lupus [40], [41].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the level of P-selectin expression in the brains of MRL/fas lpr mice may not be elevated to the same extent as has been demonstrated in several of these models, including the TNF-␣, LPS, and experimental autoimmune encephalomyelitis studies (15,35,36). It is noteworthy that measurement of P-selectin expression in various organs of MRL/fas lpr mice has shown no increase from basal levels, despite the presence of ongoing inflammation in these animals (37). This suggests that the chronic inflammatory conditions present in these mice are not conducive to increased expression of P-selectin.…”
Section: Discussionmentioning
confidence: 89%
“…Studies in SLE mouse models have shown limited vascular expression of P-selectin and E-selectin in mice at different stages of disease development, which may indicate a minor role for these adhesion molecules (27). However, it is clear from our previous work that these molecules are expressed at sufficient levels to support leukocyte rolling events in the dermal and cerebral microvasculatures in lupus-prone MRL/MpJ-Fas lpr (Fas lpr ) mice,…”
mentioning
confidence: 87%